2022
DOI: 10.3389/fcvm.2022.1059576
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondria-associated membranes mediated ROS on NLRP3 inflammasome in cardiovascular diseases

Abstract: Reactive oxygen species (ROS) metabolism is essential for the homeostasis of cells. Appropriate production of ROS is an important signaling molecule, but excessive ROS production can damage cells. ROS and ROS-associated proteins can act as damage associated molecular pattern molecules (DAMPs) to activate the NACHT, LRR, and PYD domains-containing protein 3 (NLRP3) inflammasome in cardiovascular diseases. Previous studies have shown that there are connected sites, termed mitochondria-associated membranes (MAMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 207 publications
(201 reference statements)
0
5
0
Order By: Relevance
“…It has been established that ROS-induced oxidative stress can activate NLRP3 in ammasome and initiate an in ammatory cascade implicated in disease progression. 30 In our investigation, intracellular ROS levels were signi cantly reduced after pretreatment in both the carvedilol 5uM group and the MCC950 inhibitor group compared to the ox-LDL group. The results of a recent study suggest that carvedilol suppresses the generation of ROS in breast cancer, which is consistent with the experimental ndings of this study 29 .…”
Section: Discussionmentioning
confidence: 48%
“…It has been established that ROS-induced oxidative stress can activate NLRP3 in ammasome and initiate an in ammatory cascade implicated in disease progression. 30 In our investigation, intracellular ROS levels were signi cantly reduced after pretreatment in both the carvedilol 5uM group and the MCC950 inhibitor group compared to the ox-LDL group. The results of a recent study suggest that carvedilol suppresses the generation of ROS in breast cancer, which is consistent with the experimental ndings of this study 29 .…”
Section: Discussionmentioning
confidence: 48%
“…By contrast, the activity of SOD was decreased by ox‐LDL treatment, and overexpression of 14‐3‐3‐η could restore SOD activity only with the presence of sufficient BCL‐2 (Figure 4e). Moreover, the phosphorylation of Voltage‐dependent anion‐selective channel 1 (VDAC‐1), which can be induced by increased ROS (Zhao et al, 2022), was downregulated by 14‐3‐3‐η overexpression; however, knockdown of BCL‐2 mitigated this effect (Figure 4f,g). These observations demonstrate that BCL‐2 is indispensable for 14‐3‐3‐η to reduce the oxidative stress in ox‐LDL‐treated EPCs.…”
Section: Resultsmentioning
confidence: 96%
“…We found that the level of cytochrome C, the release of which depends on ROS (Atlante et al, 2000), was significantly elevated by ox-LDL. Overexpression of 14-3-3-η efficiently attenuated the increase, but without sufficient BCL-2, excessive 14-3-3-η could no longer reduce cytochrome C ROS (Zhao et al, 2022), was downregulated by 14-3-3-η overexpression; however, knockdown of BCL-2 mitigated this effect (Figure 4f,g). These observations demonstrate that BCL-2 is indispensable for 14-3-3-η to reduce the oxidative stress in ox-LDL-treated EPCs.…”
Section: -η and Bcl-2 Expression In Epcsmentioning
confidence: 97%
“…Therefore, AA induced damage to the airway epithelium may induce rapid release of other DAMPs such as extracellular DNA or ATP, which can also activate the inflammasome ( 87 ). In addition, RAGE activation is well known to induce the rapid production of reactive oxygen species (ROS) which can also stimulate inflammasome activation ( 88 , 89 ). It also remains unclear if RAGE is required for the priming or activation steps of NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 99%